Cardiovascular and musculoskeletal assessment of elite US volleyball players - Davis, C. K.; Dyar, D. A.; Vargas, L. A.; Grossfeld, P. D. (Clinical Journal of Sport Medicine, 2015)
OBJECTIVE: The aim of this study was to characterize the cardiovascular and musculoskeletal systems of elite volleyball players, including aortic dimensions. Previous studies have shown that the upper limit of normal aortic sinus diameter for male and female athletes is 4 and 3.4 cm, respectively. DESIGN: Cross-sectional analysis. SETTING: United States Olympic Volleyball Training Facility and Rady Children's Hospital San Diego. PARTICIPANTS: Seventy (37 male) members of the US national volleyball team. MAIN OUTCOME MEASURES: Athletes underwent evaluation that included medical and family histories, targeted physical examinations specifically focusing on abnormalities present in Marfan syndrome (MFS), and transthoracic echocardiograms. Cardiac chamber and great artery size, valve function, and coronary artery origins were assessed. RESULTS: Three male athletes (8%) had an aortic sinus diameter =4 cm, one of whom also had an ascending aorta >4 cm. Two female athletes (6%) had aortic sinus diameter =3.4 cm, and another had an ascending aorta of 3.4 cm. There were no other intracardiac or arterial abnormalities. Individual musculoskeletal characteristics of MFS were common among the athletes but not more frequent or numerous in those with aortic dilation. CONCLUSIONS: The prevalence of aortic root dilation in this population of athletes was higher than what has previously been reported in other similar populations. Further study is needed to determine whether these represent pathological changes or normal variations in tall athletes. CLINICAL RELEVANCE: This study adds to the existing knowledge base of athlete's heart, with specific attention to aortic dimensions in elite volleyball players. The data are relevant to similar athletes' medical care and to preparticipation cardiac screening in general.